Resonant intuition as the driving force of emotional education - Hecker-Réz, Robert Frigyes (Acta Cultura et Paedagogicae, 2026)
In my publication, the following terms are described and structured in their interaction: emotional education, education of the heart, exchange of ideas through recurring patterns, Descartes and the doubtful, self-confident person, Pietism as the body of thought of conviction of the heart instead of beliefs; conviction of the heart as a creative force, acquisition of knowledge versus bulimia learning, personal acquisition of knowledge through emotional attachment, transforming information into applicable skills, emotional attachment as resonance ability, promotion of resonance-capable intuition.